KONSEP INTEGRASI PENDIDIKAN ISLAM DALAM PENDIDIKAN NASIONAL SEBAGAI UPAYA MENGHINDARI DIKOTOMI PENDIDIKAN DI INDONESIA - Muhamad Parhan; Rodilah Syafitri; Siti Syabana Rahmananda; Mutiara Efrillia Shanaz Aurora (IAIN Sorong, 2022)
With so many problems in education in Indonesia that still need to be resolved, one of them is the dichotomy of education in Indonesia. With this problem, the presenter conducts research using a qualitative method of literature review or literature review. The dichotomy in the education system will have a major influence on Islamic education, this will cause a complete division. Before getting too deep into the dichotomy of Islamic religious education in national education, this dichotomy must be ended immediately, one of which is by implementing the integration of Islamic education. Muslim scholars argue that this division must be repaired immediately by integrating the education system, namely by creating a third system which is also the antithesis of the traditional and modern education systems.